Ophthalmologists on Smartphones: Image-Based Teleconsultation. (9th January 2019) - Mohan, Amit; Kaur, Navjot; Sharma, Vinod; Sen, Pradhnya; Jain, Elesh; Gajraj, Manju
Background: Teleophthalmology has the potential to facilitate wider access to expert advice. It includes viewing of ophthalmic images by experts either on handheld devices like smartphones/tablets or office devices such as computer screens. However, to ensure rapid feedback, the turnaround time of any consultation must be kept to a minimum which requires use of handheld user-friendly devices. The purpose of this study was to assess whether images of different eye ailments viewed on smartphones and tablets are of comparable subjective quality as those viewed on a computer screen. Methods: This was a prospective study comparing the subjective quality of images on a smartphone, tablet and computer screen. Thirty images were analysed – 10 of extraocular morphology, 10 of the anterior segment pathology and 10 of retinal diseases. Ten ophthalmologists participated and were instructed to rate the overall quality of each image on a 7-point Likert scale (terrible-1, poor-2, average-3, fair-4, good-5, very good-6, excellent-7). Results: Overall smartphones were found to have higher ratings of subjective image quality (5.9 ± 0.48) than images displayed on tablets (5.13 ± 0.51) and computers (5.0 ± 0.37). The images were rated 'good' or 'very good' in all (100%) of the smartphone images. Fundus images and extraocular images were rated higher than anterior segment images on the smartphone. When comparing the two handheld devices with computers, both smartphones and tablets had similar image quality (p > 0.05, not significant) to computer images. However, for extraocular diseases, smartphone (6.1 ± 0.32) had significantly better image quality and images were easier to interpret compared to images on the computer (p < 0.05). Smartphones were rated 'very good' in 88.33% cases. All consultants (n = 10) were comfortable with the use of smartphone images and were already using it for teleconsultation at least three times in a month. Vision technicians reported minimum delay in getting advice when sending the images on mobile application to expert ophthalmologists. Conclusion: Smartphones can be used for teleconsultation. Subjective qualities of ophthalmic images on a smartphone are similar to those on tablets and computers. For rural communities that rely on teleconsultation, this small study provides useful evidence which may support the use of smartphones, tablets or computers for viewing ophthalmic images.